Hydrotalcite/graphene oxide hybrid nanosheets functionalized nanofiltration membrane for desalination - Wang, X.; Wang, H.; Wang, Y.; Gao, J.; Liu, Jian; Zhang, Y. (Elsevier BV, 2017)
© 2017 Elsevier B.V. An exfoliated hydrotalcite/graphene oxide (EHT/GO) hybrid nanosheet was synthesized via flocculation deposition and could be uniformly dispersed in PEI solution to be used as aqueous phase for interfacial polymerization. The process of EHT/GO flocculation and deflocculation was analyzed to gain a better understanding of its emerging mechanism. The thin-film selective layers of the hybrid membranes were formed via interfacial polymerization on the surface of PES substrate. Typically, trimesoyl chloride (TMC, 1% wt) and branched polyethyleneimine (PEI, 1.5% wt) were used as the organic phase monomer and the aqueous phase monomer. Afterwards, SEM and atomic force microscopy (AFM) were employed to characterize the morphology of the hybrid membranes and FTIR, TGA, X-ray photoelectron spectroscopy (XPS) were utilized to detect surface chemical composition of the resultant membranes. The result showed that incorporation of EHT/GO into a polyamide (PA) membrane could effectively enhance its water flux, reaching 26L/(m2h) at 0.8MPa. The salts rejection of all membranes followed the sequence: MgCl2>NaCl>MgSO4>Na2SO4, confirming that the membranes were positively charged. The rejection of EHT/GO membrane for MgCl2could reach 97.0%, which owned superior water softening performance.